PENTINGNYA MENCIPTAKAN SUASANA PEMBELAJARAN BAGI ANAK USIA DINI - Perni, Ni Nyoman (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2017)
Education is an important asset for the advancement of a nation, therefore, every citizen should and must follow the level of education, good early childhood education, primary education, secondary education or higher. In the field of education, a child from birth requires proper care in meeting the educational needs along with an understanding of the characteristics of early childhood education becomes very important and a major concern. Because of the importance of education, the parents will be held responsible how they educate their children. This will also apply for tutors, teachers or caregivers. Therefore, give the best education for our children in accordance with the development level of children, in order to be child respect for parents and teacher at the school There are four main considerations importance of early childhood education, namely: (1) prepare manpower quality (2) encourage the acceleration of the economic cycle and the low social costs (3) to improve equity in public life (4) to help parents and children.